Fungal Identifier (FId): An Updated Polymerase Chain Reaction–Restriction Fragment Length Polymorphism Approach to Ease Ascomycetous Yeast Isolates’ Identification in Ecological Studies - Silvia Abbà; Beatrice Valentini; Irene Stefanini (Journal of Fungi, 2024)
Culturomics has been temporarily exceeded by the advent of omics approaches such as metabarcoding and metagenomics. However, despite improving our knowledge of microbial population composition, both metabarcoding and metagenomics are not suitable for investigating and experimental testing inferences about microbial ecological roles and evolution. This leads to a recent revival of culturomics approaches, which should be supported by improvements in the available tools for high-throughput microbial identification. This study aimed to update the classical PCR-RFLP approach in light of the currently available knowledge on yeast genomics. We generated and analyzed a database including more than 1400 ascomycetous yeast species, each characterized by PCR-RFLP profiles obtained with 143 different endonucleases. The results allowed for the in silico evaluation of the performance of the tested endonucleases in the yeast species’ identification and the generation of FId (Fungal Identifier), an online freely accessible tool for the identification of yeast species according to experimentally obtained PCR-RFLP profiles.